Gender differences in rates of job dismissal: Why are men more likely to lose their jobs? - Roger Wilkins; Mark Wooden (Institute for the Study of Labor (IZA), 2011)
Empirical studies have consistently reported that rates of involuntary job separation, or dismissal, are significantly lower among female employees than among males. Only rarely, however, have the reasons for this differential been the subject of detailed investigation. In this paper, household panel survey data from Australia are used that also find higher dismissal rates among men than among women. This differential, however, largely disappears once controls for industry and occupation are included. These findings suggest that the observed gender differential primarily reflects systematic differences in the types of jobs into which men and women select.
urn:nbn:de:101:1-201201114005
Keywords: J16; J63; J71; 330; dismissals; gender differentials; involuntary job separations; HILDA Survey; Australia; Kündigung; Geschlecht; Beruf; Männliche Arbeitskräfte; Schätzung; Australien